The conquest of Santarém and Goswin's song of the conquest of Alcácer do Sal : editions and translations of De expugnatione Scalabis and Gosuini de expugnatione salaciae carmen /: editions and translations of De expugnatione Scalabis and Gosuini de expugnatione salaciae carmen. (2021) - Wilson, Jonathan
No abstract available